(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
This study presents a single-element 2-port multiple-input multiple-output (MIMO) Dielectric Resonator Antenna (DRA) with enhanced bandwidth. By introducing a central notch and side cutouts in the DRA structure, the antenna achieves an impedance bandwidth of 27.4-29.8 GHz, effectively covering the n257 (28 GHz) band. Orthogonal excitation and a metallic via inside the DRA ensure an isolation level greater than 15.6 dB across the entire operational bandwidth. The antenna delivers a peak gain of 5 dBi with a radiation efficiency of up to 96%. The MIMO performance metrics fall within acceptable limits, making the design highly suitable for mm-wave 5G applications. Its single-element configuration and aperture feeding contribute to a compact and straightforward design.